ANALISIS TINGKAT KESEHATAN KOPERASI PADA KOPERASI SYARIAH BAITUL QIRADH SURYA MADINAH BANDA ACEH TAHUN BUKU 2009-2010 - Aliamin - (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2012)
The health assessment of Microfinance Institutions (MFIs) is a cooperative incorporated descriptive research study that aims to get the description of health BQ Surya Madinah (Islamic MFIs). The period for this study was raised in 2009 and 2010. The guidelines for use of cooperative health assessment, formulated by the Ministry of Cooperatives and Small and Medium Enterprises Republic of Indonesia, which poured through the Minister's decision No. 35.3/Per/M.KUKM/X/2007 for cooperative health assessment sharia. In a co-operative health assessment consists of eight aspects of sharia that aspects of capital valuation, asset quality, management, efficiency, liquidity, and growth kemadirian, cooperative identity, sharia compliance. However, in this study only four financial ratios studied the aspects of capital, asset quality, liquidity, and the independence and growth.             The results calculation (score) of each component aspect ratio shows the ratio of the components are not all aspects can be expressed well, only three ratios that can yield the best assessment of the capital adequacy ratio of the given conclusion score "HEALTHY" financial ratios for the funds received were conclusions scores "LIQUID" profitability and capital ratios are given conclusion score "HIGH".To obtain better achievements in the future, it requires a proper measures to raise awareness of all members of the cooperative to jointly participate in the implementation of cooperative activities, either in the form of capital, financing and deposits. Key words: health assessment, Islamic MFIs, and BQ Surya Madinah